Efektivitas Bahan Ajar Persamaan Differensial Berbasis Problem Based Learning pada Pokok Bahasan Persamaan Diferensial - Rofiroh Rofiroh; Yani Setiani; Linda (Cakrawala Pedagogik, 2025)
This study aims to test the effectiveness of Differential Equations (PD) teaching materials based on Problem Based Learning (PBL). The main component of teaching materials is a medium to bridge the curriculum with students' learning experiences. The current PD lecture conditions are still dominated by 56% of lecture methods. This results in students having difficulty in understanding applicable concepts and mastering mathematical modeling skills. The research method used is quantitative with a quasi-experimental approach tested on 25 third-semester PD course students. The effectiveness of teaching materials was tested using N-gain analysis and Wilcoxon Signed Rank Test. The results of the study showed a significant increase in the average value from the pre-test (17.24) to the post-test (75.36). The average N-gain of 0.81 is categorized as high. The results of the Wilcoxon Test showed an Asymp.Sig (2-tailed) value of 0.00 <0.05. This means that there is a significant difference between the values ??before and after the use of PBL teaching materials. This is evident from the fact that 92% of students agreed that PBL learning materials can improve their thinking skills in solving PD problems.